Prevalence of poor sleep quality and associated factors among the elderly in Amirkola, Iran - Seyed Reza Hosseini; Mostafa Dezhalon; Reza Ghadimi; Ali Bijani; Ali Zabihi (Health for All Nations, 2023)
Background & Aims: Sleep problems have become the most common complaint among the elderly. Various factors are involved in the prevalence of poor sleep quality in this age group. Due to the lack of community-based data, this study was conducted to determine the prevalence of poor sleep quality among the elderly in Amirkola, Northern Iran. Methods: This cross-sectional study is part of the second phase of the Amirkola Health and Ageing Project (AHAP), a cohort study conducted on all elderly aged 60 and over in Amirkola, Northern Iran, since 2011. The sleep quality and related factors were assessed through Pittsburgh Sleep Quality Index (PSQI-P) and interviews, respectively. Results: Of the 1675 older people, 914 (54.6%) were male, and 761 (45.4%) were female, of whom 714 (42.6%) had poor sleep quality. The prevalence of poor sleep quality in women and men was 56.9% and 30.7%, respectively (p <0.001). Poor sleep quality was significantly more frequent among unmarried elderly (50.4%) (p = 0.004), those with lower education level (p<0.001), individuals who were living alone (51.3%) (p<0.001), and those with more chronic disease (p<0.001), compared to other groups. Older men with diabetes had more poor sleep quality (p=0.048). Also, poor sleep quality was significantly related to depression and the number of chronic diseases in both men and women (p<0.001). Logistic regression analysis revealed that the female sex (OR=2.34, 95% CI (2.85-95.95)) and chronic diseases (OR=4.48, 95% CI (2.02-9.93)) had the most important roles in poor sleep quality. Conclusion: This study showed a relatively high prevalence of poor sleep quality in older people, particularly among females. Therefore, sleep quality inquiry of the elderly seems pivotal in routine public health assessments by physicians and health care providers.